PENGARUH CURRENT RATIO, RETURN ON ASSET, DAN DEBT TO EQUITY RATIO TERHADAP HARGA SAHAM PERUSAHAAN MAKANAN DAN MINUMAN DI BURSA EFEK INDONESIA PERIODE 2015-2017 - Anna, Anna; Asakdiyah, Salamatun (Universitas Ahmad Dahlan, 2018)
The research was conducted to test the current, ratio return on assets, and debt to equity ratio on the price of food and beverage company shares in the indonesia stock exchange. 2015-2017 periodThis peneltian mengetaui (1) is there to influence current ratio, stock prices (2) is there the return on assets against, stock prices (3) is there the influence of debt to equity ratio of, stock prices (4) does influence together current, ratio return on assets, and debt to equity ratio on the price of food and minumana shares in companies listed on the indonesia stock exchange. 2015-2017 period. The population in this study is a food and beverage company listed on the IDX. The sample selection uses a purposive sampling method. The total sample of 11 food and beverage companies is listed on the IDX in the period 2015-2017. Data analysis using classical assumption test and panel data model regression analysis. Based on the results of the study show that (1) Current Ratio partially has a positive and not significant effect on stock prices, (2) Return on Asset partially has a positive and significant effect on stock prices, (3) Debt to Equity Ratio partially has a negative effect and not significant to stock prices, (4) Current Ratio, Return on Assets, and Debt to Equity Ratio simultaneously have a positive and significant effect on stock prices, this is evidenced by the R2 value of 0.322021 and F significance value of 4.591398.